ANALISIS STRUKTUR RANGKA BAJA MENGGUNAKAN BASE ISOLATION DENGAN TIME HISTORY ANALYSIS - Saloma, Saloma (CANTILEVER, 2015)
This paper discussed the usage of base isolation in the form of leading rubber bearing which is applicated on steel structure of five floor. The analysis is done on steel structure by using base isolation. It is compared with steel structure without base isolation. The usage of base isolation on steel structure with loading earthquake can reduce response structure either displacement, velocity or accelaration.Key Words: base isolation, lead-rubber bearing.